CONFLICT MANAGEMENT AND SUCCESSION IN FAMILY-OWNED SMALL BUSINESSES - Brown, Crystal H. M. (International Journal of Research -GRANTHAALAYAH, 2022)
Family-owned small businesses generate approximately 44% of all U.S. economic activity making them essential to the nation’s economic health. Unfortunately, they often struggle with a variety of challenges, including succession. While the development of models and theoretical understandings of how succession may occur in family-owned small businesses is helpful for extending the related body of literature, practical research is needed to better understand the ways succession is handled among the key stakeholders, including the incumbent, the successor, and the family. The purpose of this qualitative multiple case study was to explore conflict management and succession strategies employed by leaders and employees of family-owned small businesses. Data were collected via interviews with nine people from three family-owned small businesses located in the upper Midwestern United States. A total of five main themes emerged, including Employees’ perceptions and their communication styles determine succession strategies, the nature of succession depends on communication, fostered succession through keeping customers happy and succession planning, succession challenges that leaders and employees encounter, and success was demonstrated by internal and external motivators. Eight subthemes emerged, including keep customers happy, agreeable communication, succession planning, knowledge sharing, conflict, motives, do what needs to be done, and commitment to organization. Findings from this study shed light on ways conflict management and succession strategies employed in family-owned small businesses may be improved to help these businesses overcome common challenges and ensure survival from one generation to the next.